Inculcation Of Spiritual Values Through Extracurricular Activities Tahfidz AlQur'an: PENANAMAN NILAI-NILAI SPIRITUAL MELALUI KEGIATAN EKTRAKULIKULER TAHFIDZ AL-QUR’AN - Subawaihini, Imam (Konsorsium Dosen Sekolah Tinggi Agama Islam (STAI) Al-Yasini Pasuruan, 2023)
This study aims to instill spiritual values in the form of character through extracurricular activitiestahfidz Al Qur'an. The method used is descriptive qualitative with data collection techniques in the form ofobservation, interviews, and documentation. The results of this study include students using one type ofmushaf, understanding the meaning of the content of the memorized verse, not moving to the next verse if ithas not been memorized and using the talaqqi method in its implementation strategy. The spiritual valuesinstilled include students' courtesy to teachers, mutual respect for friends, and discipline. Supporting factorsare adequate infrastructure, competent teachers, and student motivation. Meanwhile, the inhibiting factoris students' laziness and lack of patience, as well as students' lack of understanding of the laws of reading andmakhrojul letters. So the cultivation of spiritual values through extracurricular tahfidz Al Qur'an will besuccessful if all these components and conditions are carried out.Keywords: Spiritual Value, Extracurricular Tahfidz Al-Qur'an